2008
DOI: 10.1136/pgmj.2007.067389
|View full text |Cite
|
Sign up to set email alerts
|

Phasic characteristics of inspiratory crackles of bacterial and atypical pneumonia

Abstract: In patients with CAP and audible crackles, phasic characteristics of inspiratory crackles may be used to distinguish AP from BP. Prospective studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…SP-P was associated with a shorter length of respiratory symptoms before ICU admission (3 days [2-7] vs. 6 days [4][5][6][7][8][9], p = 0.0008). At ICU admission SAPS II score was higher for SP-P (42 [30-55] vs. 32 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], p = 0.005), shock was more frequent (32% vs. 8%; p = 0.0004), creatinine level was higher (101 [69.5-168.8] μmol/L vs. 77 [57.5-108] μmol/L, p = 0.008), and lactate level was high (2.3 [1.8-3.4] mmol/l vs. 1 [0.07-2.7] mmol/l; p = 0.003).…”
Section: Outcomes Of Atypical Pneumonia (Ap)mentioning
confidence: 99%
“…SP-P was associated with a shorter length of respiratory symptoms before ICU admission (3 days [2-7] vs. 6 days [4][5][6][7][8][9], p = 0.0008). At ICU admission SAPS II score was higher for SP-P (42 [30-55] vs. 32 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], p = 0.005), shock was more frequent (32% vs. 8%; p = 0.0004), creatinine level was higher (101 [69.5-168.8] μmol/L vs. 77 [57.5-108] μmol/L, p = 0.008), and lactate level was high (2.3 [1.8-3.4] mmol/l vs. 1 [0.07-2.7] mmol/l; p = 0.003).…”
Section: Outcomes Of Atypical Pneumonia (Ap)mentioning
confidence: 99%
“…On physical examination, more than half of the patients with Mp pneumonia had no audible crackles and were likely to have late inspiratory crackles . Therefore, primary care physicians should be aware of these six factors that help discriminate Mp pneumonia from other causes of CAP using the JRS “diagnostic tests” (Table ).…”
Section: Mp Pneumoniamentioning
confidence: 99%
“…Goto (2011) reported that the mean body temperature in adult Japanese patients with Mp pneumonia was 37.7 ± 1.0°C and that 29.2% of patients had a temperature no greater than 37.0°C. Analysis of physical examination data revealed that more than half of patients with Mp pneumonia had no audible crackles and were likely to have late-inspiratory crackles as compared with those infected with typical pathogens (Norisue et al, 2008). On laboratory examination, Mp pneumonia patients had relatively lower leukocyte counts than did those having pneumonia from other causes (Von Baum et al, 2009).…”
Section: Clinical Featuresmentioning
confidence: 99%